2018
DOI: 10.14202/vetworld.2018.379-385
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Shiga toxin-producing Escherichia coli harboring variant Shiga toxin genes from seafood

Abstract: Background and Aim:Shiga toxin-producing Escherichia coli (STEC) are important pathogens of global significance. STEC are responsible for numerous food-borne outbreaks worldwide and their presence in food is a potential health hazard. The objective of the present study was to determine the incidence of STEC in fresh seafood in Mumbai, India, and to characterize STEC with respect to their virulence determinants.Materials and Methods:A total of 368 E. coli were isolated from 39 fresh seafood samples (18 finfish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Numerous studies have reported both O157 and non-O157 STEC in fresh fish and shellfish, and their ready-to-eat products in retail markets (Thampuran et al, 2005;Surendraraj et al, 2010;Prakasan et al, 2018), suggesting that human activities, such as handling, processing, and ingestion of the products might be a major source of STEC contamination. Interestingly, fish and shellfish residing in coastal areas, some cultured fish, and those in close proximity to or downstream of animal livestock facilities have been found to be contaminated with STEC (Gourmelon et al, 2006;Sekhar et al, 2017;Cardozo et al, 2018;Siddhnath et al, 2018;Hussein et al, 2019).…”
Section: Emerging Reservoirs Of Stec and Needs For The One Health Approachmentioning
confidence: 99%
“…Numerous studies have reported both O157 and non-O157 STEC in fresh fish and shellfish, and their ready-to-eat products in retail markets (Thampuran et al, 2005;Surendraraj et al, 2010;Prakasan et al, 2018), suggesting that human activities, such as handling, processing, and ingestion of the products might be a major source of STEC contamination. Interestingly, fish and shellfish residing in coastal areas, some cultured fish, and those in close proximity to or downstream of animal livestock facilities have been found to be contaminated with STEC (Gourmelon et al, 2006;Sekhar et al, 2017;Cardozo et al, 2018;Siddhnath et al, 2018;Hussein et al, 2019).…”
Section: Emerging Reservoirs Of Stec and Needs For The One Health Approachmentioning
confidence: 99%
“…The main route of STEC transmission to humans is the consumption of contaminated food, traditionally beef (Kintz et al., 2017). Nevertheless, in recent years there have been increasing reports of illness associated with the consumption of vegetables, seafood, ready‐to‐eat products (RTEP) and other foods (Erickson & Doyle, 2007; Prakasan et al., 2018; Torres et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Although E. coli is popular as an indicator of faecal contamination of water and foods, it is a significant food-borne human pathogen [1]. Contamination of seafood with E. coli as a consequence of contamination of coastal waters with domestic sewage is common in densely populated countries like India [2,3]. Such pathogenic E. coli can cause a range of infections, such as gastroenteritis, wound infections, septicaemia, urinary tract infections, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Post-harvest contamination of seafood with E. coli occurs in fish landing centres and markets. Past studies from India have reported the isolation of various pathogroups of E. coli from seafood [ 3 , 17 , 18 , 19 ] and also the presence of highly antibiotic resistant E. coli , such as the bla NDM -harbouring strains [ 20 , 21 , 22 ]. In the study reported here, we investigated the prevalence of antibiotic resistance in Escherichia coli isolated from seafood and the genetic factors responsible for resistance.…”
Section: Introductionmentioning
confidence: 99%